A pH-sensitive nanoagent self-assembled from a highly negatively-charged phthalocyanine with excellent biosafety for photothermal therapy. Issue 12 (11th March 2021) - Zheng, Bing-De; Huang, Zhen-Liang; Lv, Li-Li; Lan, Wen-Liang; Hu, Jia-Qian; Li, Xingshu; Zheng, Bi-Yuan; Ke, Mei-Rong; Huang, Jian-Dong
Abstract : A negative-charged and pH-sensitive nanoagent self-assembled from a multisulfonate-substituted phthalocyanine was prepared, which showed highly efficient photothermal anticancer efficacy with very low accumulation in liver and excellent biosafety. Abstract : Photothermal therapy (PTT) is a promising strategy for cancer treatment. However, the development of highly efficient photothermal agents with excellent biosafety, particularly with low liver retention, is very meaningful for clinical applications, but it is also challenging. We herein prepared a pH-sensitive nanoagent (NanoPc3 ) by the self-assembly of a zinc(ii ) phthalocyanine substituted with hexadeca-sulphonates linked by hydrazone bonds for photoacoustic imaging and PTT. Due to the highly negative surface potential (−30.80 mV in water), NanoPc3 could effectively escape the phagocytosis of the reticuloendothelial system and be rapidly cleared from normal tissues, leading to little accumulation in the liver and excellent biosafety. The highly negatively-charged NanoPc3 changed into nearly neutral nanoparticles (NanoPc3H ) under slightly acidic conditions, resulting in enhanced cellular uptake and retention time in tumor tissues. Moreover, the tumor of H22 tumor-bearing mice treated with NanoPc3 almost disappeared, suggesting an outstanding photothermal antitumor effect. NanoPc3 also hardly showed skin phototoxicity under irradiation. Its excellent antitumor effect and biosafety make NanoPc3 highly promising in clinical applications. This work will provide a new strategy for the design of tumor-targeted photothermal nanoagents with high biosafety.